The Potential of Criminal Sanctions in Indonesia’s Spatial Planning Law from a Sustainable Development Perspective - Aprila Niravita; Masyhar, Ali; Rodiyah, Rodiyah; Suhadi, Suhadi; Chhachhar, Varun; Adymas Hikal Fikri, Muhammad (Indonesian Journal of Environmental Law and Sustainable Development, 2025)
This study examines the role of criminal law in curbing unlawful land-use practices in Indone-sia's broader spatial-planning framework. Its primary interest lies not only in asking whether the threat of criminal enforcement deters potential offenders but also in investigating whether those who violate the rules receive sanctions that are credible, consistent, and sufficiently severe. Employing a normative legal methodology, the author examines statutory texts, cornerstone legal principles, and leading judicial opinions, deftly navigating between major codes and significant academic commentary. The analysis shows that although sanctions appear to be codified, they operate with limited force in the real world because of vague language, poorly trained investigators, and an enduring pattern within government agencies to rely on softer administrative fines before resorting to stricter penalties. On that ground, the paper insists that criminal tools must still act as an ultimum remedium if Indonesia hopes to defend the rule of law and head toward truly sustainable land management. To make the system stronger, the author(s) calls on lawmakers to clarify enforcement paths, improve coordination between ministries, and fund training for the officers who face spatial violations day after day.